Ketofol: A ketamine‐propofol admixture for induction of anaesthesia in two foals. Issue 3 (29th June 2021) - Sun, Tsim Christopher; Bellei, Maria; Robinson, Alexandra; Martinez‐Taboada, Fernando
Abstract: Two foals undergoing surgery for angular limb deformities were anaesthetised using ketamine:propofol admixture (ketofol). Ketamine was used at 2 and 1 mg/kg, and propofol at 2 and 1.5 mg/kg in cases 1 and 2, respectively. Induction of general anaesthesia was smooth and occurred within 30 seconds after ketofol administration. No apnoea, nystagmus and paddling were noted. In case 1, anaesthesia was maintained with additional boluses of propofol (0.4 mg/kg) and flow‐by oxygen delivered via face mask, and in case 2 with isoflurane delivered in oxygen. The anaesthetic time was 20 and 55 minutes in cases 1 and 2, respectively. Before recovery, xylazine (0.2 mg/kg) was administered IV in case 2. Both foals stood at the first attempt approximately 10 minutes later with mild ataxia. Ketofol could be an alternative for induction of anaesthesia in foals. Further studies are warranted to understand the effects of ketofol especially in comparison to ketamine‐benzodiazepine combinations.